The impact of self-efficacy, entrepreneurial motivation, and entrepreneurship education on interest in entrepreneurship - Reinaldi William; Rodhiah Rodhiah (Sultan Publisher, 2024)
Entrepreneurial interest in entrepreneurs is important because it can influence and impact several aspects, especially the economic aspects of oneself, other people, and the country. Entrepreneurship education, self-efficacy, and motivation can influence a person’s interest in entrepreneurship. The purpose of this research is to identify and understand the factors that can affect the entrepreneurial interest of students at the Faculty of Economics and Business, Tarumanagara University. This research uses quantitative methods. The sample selection technique used a non-probability sampling method. The population and sample were all students from the Faculty of Economics and Business, Tarumanagara University, totalling 100 respondents. The data collection method used an online questionnaire via the Google platform. The scale used is the Likert Scale. The testing of the data analysis technique is Partial Least Square-Structural Equation Modelling (PLS-SEM), which consists of two analyses, namely the outer model, which consists of validity and reliability, and an inner model for data analysis. The results of this study indicate that entrepreneurship education, self-efficacy, and motivation can influence students' interest in entrepreneurship. The results of the entrepreneurship education analysis show a T-statistic value of 3.724 and p-value of 0.000. The results of the self-efficacy analysis show a T-statistic value of 2.157 and p-value of 0.031, indicating that self-efficacy can increase interest in entrepreneurship. The results of the analysis of entrepreneurial motivation showed a T-statistic value of 2.761 and a p-value of 0.000.